Perumusan Strategi Pemasaran - Fahmy Rizky Ramadhani; Seno Sumowo; Ahmad Izzudin (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine the formulation of marketing strategies at the Yamaha Iron Cycles Jember workshop. This research method is descriptive qualitative research. Some of the data obtained will be numbered to facilitate the merging of two or more variable data then after the final results are obtained, they will be requalified. In this study, the data analysis tool used SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The results showed, in the IE matrix, it was shown that the Yamaha Iron Cycles Workshop applied the strategy using the Growth Oriented Strategy. This is because the IE matrix shows that the highest total score is in the first quadrant, which is a very favorable situation in this quadrant. In conclusion, the Yamaha Iron Cycles Workshop has many opportunities and strengths that can be optimized so that it can overcome the threats and weaknesses that occur in the Jember Iron Cycles Yamaha Workshop. Keywords: External Factors, Internal Factors, Strategic Management, SWOT Matrix